The Influence of Listener Personality on Music Choices - Kleć, Mariusz (Computer Science, 2017)
To deliver better recommendations, music information systems need to go beyond standard methods for musical taste prediction. Tracking the listener’s emotions is one way to improve the quality of recommendations. This can be achieved explicitly, by asking the listener to report his/her emotional state, or implicitly, by tracking the context in which the music is heard. However, the factors that induce particular emotions vary among individuals. This paper presents initial research on the influence of an individual’s personality on his or her choice of music. The psychological profile of a group of 16 students was determined by a questionnaire. The participants were asked to label their own music collections, listen to the music, and mark their emotions using a custom application. Statistical analysis revealed correlations between low-level audio features, personality types, and emotional states of the students.